The The Impact of Changes in Wife’s Employment Status on Household Stability: A Review of Islamic Family Law - Lina Nur Anisa (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
The changing employment status of wives in Muslim households has become a significant social phenomenon impacting family dynamics, especially within Islamic family law. Increasing female workforce participation brings complex shifts in roles, responsibilities, and obligations of spouses, affecting household stability economically and socially. This study explores how Islamic family law responds to and regulates these changes, considering cultural and legal challenges posed by formal employment, such as Government Employees with Work Agreements (PPPK) and Civil Servants (PNS), versus informal employment. The research uses a qualitative library method, analyzing primary and secondary sources including books, journals, fatwas, and legal documents on Islamic family law. Through content and critical analysis, it synthesizes normative legal perspectives with empirical data—especially the mass divorce cases in Blitar and Cianjur—to understand the multifaceted impact of wives’ employment changes on household harmony. Findings highlight that while Islamic law keeps the husband as primary provider, it allows flexibility in recognizing productive roles of working wives, provided family harmony is preserved. The study underscores supportive spousal communication, psychosocial adaptation, and contextual legal interpretation to reduce conflicts from role changes. It concludes an integrative approach involving adaptive legal frameworks, family education based on Islamic values, and responsive social policies is essential to maintain Muslim family stability amid modern socio-economic transitions. This research offers valuable insights for academics, legal practitioners, and policymakers balancing tradition and modernity in Muslim family life.